A Zr-based metal organic frameworks towards improving fire safety and thermal stability of polycarbonate. (1st November 2019) - Sai, Ting; Ran, Shiya; Guo, Zhenghong; Fang, Zhengping
Abstract: Zr-based metal organic frameworks (Zr-BDC) with high porosity were synthesized by a solvothermal method and then compounded with polycarbonate (PC, one of the most important engineering plastic) to reduce the fire hazard and improve the thermal stability of PC. It was found that Zr-BDC could prolong the time to ignition (TTI) and time to peak of heat release rate (t-PHRR) of PC up to 90 and 75 s, respectively. Compared with the neat PC, 2 wt% Zr-BDC could increase the temperature at the maximum degradation rate ( T max ) of PC in N2 atmosphere by 33 °C; 4 wt% Zr-BDC reduced the values of peak heat release rate (PHRR) and total smoke release (TSR) by 48% and 34%, respectively. Moreover, only 4 wt% Zr-BDC made the composites reach UL-94 V-0 rating in vertical burning test. Unsaturated Zr metal site made Zr-BDC have activity in catalytic oxidation, isomerization reactions etc., which imparted it the ability to catalyze char formation (cross-linking) in the degradation process of PC matrix, therefore more compact, and highly graphitized char layers were obtained.